Penerapan Sanksi Terhadap Pelaku Tindak Pidana Pembunuhan Berencana Berdasarkan Putusan Nomor : 1298/PID.B/2018/PN.DPS - Kadek Desy Pramita; I Gusti Ketut Riski Suputra (Jurnal Pacta Sunt Servanda, 2021)
One of the acts that often occurs in human life in society is a crime against life or often called murder. Murder can be classified into four types, one of which is premeditated murder. Like what I Wayan Siki did to his colleagues in the decision number: 1298 / PID.B / 2018 / PN.DPS. To prove that the act committed by the defendant was premeditated murder, it is necessary to have a correlation between Article 340 of the Criminal Code concerning premeditated murder and the elements of the perpetrator's act. This research uses empirical juridical method, with a correlational approach and data collection techniques, namely literature study and document study. And it was found that the criminal acts committed by the defendants were in accordance with the elements of Article 340 of the Criminal Code. So that the perpetrator's action can be declared as an act of planned murder, and the verdict given by the judge is appropriate.